THE CONCEPT OF EDUCATIONAL LEADERSHIP KI HAJAR DEWANTARA - Asri Yuni Vika Sari; Machdum Bachtiar, Anis Fauzi (Adisam Publisher, 2023)
The success of an organization is determined by the leader of that organization. The leader becomes the driving force of the organization in order to develop and achieve the goals that have been set. The purpose of writing this article is to explain the implementation of the Ki Hajar Dewantara leadership model through the concept of education of the Ki Hajar Dewantara Trilogy which contains three important principles: Ing ngarsa sung tuladha, ing madya mangun karsa, tut wuri handayani. The method used in this article is qualitative, while the approach is literature study. The author obtained information about the leadership model of Ki Hajar Dewantara through searching for articles in national and international journals with the keyword